2012
DOI: 10.1002/erv.2212
|View full text |Cite
|
Sign up to set email alerts
|

The Facial and Subjective Emotional Reaction in Response to a Video Game Designed to Train Emotional Regulation (Playmancer)

Abstract: Several aspects of social and emotional functioning are abnormal in people with eating disorders. The aim of the present study was to measure facial emotional expression in patients with eating disorders and healthy controls whilst playing a therapeutic video game (Playmancer) designed to train individuals in emotional regulation. Participants were 23 ED patients (11 AN, 12 BN) and 11 HCs. ED patients self reported more anger at baseline but expressed less facial expression of anger during the Playmancer game.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 26 publications
1
35
0
1
Order By: Relevance
“…Although preliminary, the results suggest that this approach has potential for providing patients with additional coping skills for managing negative emotions and stress. Another study measured the facial expression of emotion in 23 patients with eating disorders compared to 11 healthy controls during PlayMancer game-play [79]. These authors found that patients with eating disorders reported more anger at baseline but showed less facial expression of anger during the PlayMancer game.…”
Section: Prospective Studies-cognition and Mental Healthmentioning
confidence: 96%
“…Although preliminary, the results suggest that this approach has potential for providing patients with additional coping skills for managing negative emotions and stress. Another study measured the facial expression of emotion in 23 patients with eating disorders compared to 11 healthy controls during PlayMancer game-play [79]. These authors found that patients with eating disorders reported more anger at baseline but showed less facial expression of anger during the PlayMancer game.…”
Section: Prospective Studies-cognition and Mental Healthmentioning
confidence: 96%
“…In anorexia nervosa (AN) n=6; bulimia nervosa (BN) n=1; AN/BN n=4 (Cardi et al, 2015(Cardi et al, , 2014Claes et al, 2012;Dapelo et al, 2015;Davies et al, 2013Davies et al, , 2011Lang et al, 2016;Rhind et al, 2014;Soussignan et al, 2011Soussignan et al, , 2010Tárrega et al, 2014).…”
Section: Eating Disorders (Ed)mentioning
confidence: 99%
“…Results were similar for both outcome measures, but since Duchenne-smiles are considered a more authentic expression of positive emotion, these outcome values were included in the meta-analysis. This resulted in six ES for quantitative synthesis for positive emotions and five for negative emotions (Dapelo et al (2015) The remaining four studies in ED (Claes et al, 2012;Soussignan et al, 2011Soussignan et al, , 2010Tárrega et al, 2014) were shown prior to the food pictures (d=0.9). Soussignan et al (2011) also used food stimuli in comparison to non-food stimuli with comparative hedonic value and measured EMG response of zygomaticus and corrugator activity.…”
Section: Eating Disorders (Ed)mentioning
confidence: 99%
See 1 more Smart Citation
“…Patients suffering from anorexia nervosa can feel anger as a terrifying emotion that needs to be avoided (by concentration on food, body and weight), needs to be suppressed, for example by physical activity, and released by anorectic self-control or self-harm (Espeset, Gulliksen, Nordbø, Skårderud, & Holte, 2012). They tend to show less facial anger expression than they feel, which may lead to problems in social communication (Claes et al, 2012;Joos et al, 2012). It is suggested that treatment of non-suicidal self-injury in ED should focus on stabilizing affective states rather than on reducing affects like anger (Vansteelandt et al, 2013).…”
Section: Introductionmentioning
confidence: 99%